Allogeneic T cells impair engraftment and hematopoiesis after stem cell transplantation - Müller, Antonia M. S. (National Academy of Sciences, 2010)
Because of the perception that depleting hematopoietic grafts of T cells will result in poorer immune recovery and in increased risk of graft rejection, pure hematopoietic stem cells (HSC), which avoid the potentially lethal complication of graft-versus-host disease (GVHD), have not been used for allogeneic hematopoietic cell transplantation (HCT) in humans. Ideal grafts should contain HSC plus mature cells that confer only the benefits of protection from pathogens and suppression of malignancies. This goal requires better understanding of the effects of each blood cell type and its interactions during engraftment and immune regeneration. Here, we studied hematopoietic reconstitution post-HCT, comparing grafts of purified HSC with grafts supplemented with T cells in a minor histocompatibility antigen (mHA)-mismatched mouse model. Cell counts, composition, and chimerism of blood and lymphoid organs were evaluated and followed intensively through the first month, and then subsequently for up to 1 yr. Throughout this period, recipients of pure HSC demonstrated superior total cell recovery and lymphoid reconstitution compared with recipients of T cell-containing grafts. In the latter, rapid expansion of T cells occurred, and suppression of hematopoiesis derived from donor HSC was observed. Our findings demonstrate that even early post-HCT, T cells retard donor HSC engraftment and immune recovery. These observations contradict the postulation that mature donor T cells provide important transient immunity and facilitate HSC engraftment.